Metode Dakwah Digital Prespektif Studi Hadist - Muhammad Fikri ‘Ainun Najib, ainun Fikri; Rohman, miftakhul (Universitas Nahdlatul Ulama Blitar, 2024)
Hadith Study Perspective Digital Da'wah Method. Dakwah is an attempt to invite people to the path of Allah. In the study of da'wah philosophy, the term ontology of da'wah is known. Ontology is the science of being. Whereas the ontology of da'wah discusses things that exist or the source of everything, so in the application of da'wah, the sources of da'wah are the Koran and hadith, so it is necessary to pay attention to what is the source. So that it can add to the treasury of knowledge for preachers. At this time da'wah has developed into the digital world, which is commonly referred to as digital da'wah. The use of social media is an alternative means that is possible in the midst of current policies. With social media we can expand the target of da'wah to be addressed, therefore the author discusses this theme to strengthen social media as a means of da'wah.